Critical discourse analysis of model Teun Van Dijk in Liputan6.com news media "Prabowo woos the TikTok generation with gemoy dance for 2024 election" - Hariyanto, Edy (Maliki Interdisciplinary Journal, 2024)
This study describes the text dimension of Teun A Van Dijk’s model in online news discourse on liputan6.com with the title "Prabowo Woos the TikTok Generation with Gemoy Dance for 2024 Election" on December, 3 2023. This research data is a speech on online media liputan6.com, while the source of the data is an online newspaper liputan6.com in the form of news text about Prabowo Woos the TikTok Generation with Gemoy Dance for 2024 Election. Data collection methods and techniques use documentation methods with listen and record techniques, while data analysis methods use content analysis methods with critical discourse analysis approaches Teun A Van Dijk model. The results of the study found that the news contained three dimensions of text based on Teun A Van Dijk’s theory. The three dimensions are superstructure dimensions, macrostructure, and microstructure. However, this study only discusses micro-dimensions / superstructures which include semantics (background, intent and details) and syntax (main sentences, descriptive sentences, quotation sentences, predicative sentences, coherence, and pronouns).